(untitled) - J.K.Rowling (London Bloomsbury Publishing, 2014)
The sixth adventure in the spellbinding Harry Potter saga - the series that changed the world of books forever When Dumbledore arrives at Privet Drive one summer night to collect Harry Potter, his wand hand is blackened and shrivelled, but he does not reveal why. Secrets and suspicion are spreading through the wizarding world, and Hogwarts itself is not safe. Harry is convinced that Malfoy bears the Dark Mark: there is a Death Eater amongst them. Harry will need powerful magic and true friends as he explores Voldemort's darkest secrets, and Dumbledore prepares him to face his destiny. These classic editions of J.K. Rowling's internationally bestselling, multi-award-winning series feature thrilling jackets by Jonny Duddle, bringing Harry Potter to the next generation of young readers. It's time to PASS THE MAGIC ON ...
Keywords: Young Adult; Magic; Adventure; Science Fiction; Childrens; Fantasy